2022
DOI: 10.1002/anie.202207130
|View full text |Cite
|
Sign up to set email alerts
|

Aminal‐Linked Porphyrinic Covalent Organic Framework for Rapid Photocatalytic Decontamination of Mustard‐Gas Simulant

Abstract: Covalent organic frameworks (COFs) are appealing photocatalysts for toxic chemical degradation. Great efforts have been devoted to regulate the photocatalytic performance of COFs by tuning their organic building blocks, but the relationship between COF linkage and photochemical properties has rarely been explored. Herein, we report the synthesis and characterisation of a novel aminal-linked porphyrinic COF, namelyPor-Aminal-COF.Por-Aminal-COF (0.25 mol %) showed excellent photocatalytic activity toward the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 60 publications
0
47
0
Order By: Relevance
“…Therefore, it is important to develop efficient decontamination methods for the removal of mustard gas from the environment. Zang et al 111 reported an amine-linked porphyrin COF with 5,10,15,20- tetrakis(4-benzaldehyde)porphyrin and piperazine as monomers (Fig. 16).…”
Section: Cofs For Photocatalytic Environmental Remediationmentioning
confidence: 99%
“…Therefore, it is important to develop efficient decontamination methods for the removal of mustard gas from the environment. Zang et al 111 reported an amine-linked porphyrin COF with 5,10,15,20- tetrakis(4-benzaldehyde)porphyrin and piperazine as monomers (Fig. 16).…”
Section: Cofs For Photocatalytic Environmental Remediationmentioning
confidence: 99%
“…16,[26][27][28][29] Essentially, the high CEES degradation activity of ZZU-601 and ZZU-602 is related to their photogenerated singlet oxygen ( 1 O 2 ) efficiency. 16,30 Electron paramagnetic resonance (EPR) trapping measurements were initially carried out to monitor the generation of 1 O 2 . As expected, with 2,2,6,6-tetramethylpiperidine (TEMP) as a trapping agent, 16,31 a typical 1 : 1 : 1 triplet signal of the TEMP-1 O 2 adduct was detected in the presence of SCC-MOFs upon light irradiation (Fig.…”
Section: S5 Esi †)mentioning
confidence: 99%
“…Extensive work has demonstrated that detoxification of nerve agents through hydrolysis of labile P–X bonds (X = F, CN, S, etc.) is a promising route, while for the degradation of mustard gas, selective oxidation to sulfoxide is an effective approach. ,, Realistically, the CWAs deployed in war are usually unknown and deadly; hence, to efficiently prevent harm to human beings caused by CWAs, multifunctional catalysts that simultaneously detoxify various types of CWAs are highly desired. However, the different detoxification pathways make constructing versatile catalysts quite challenging.…”
Section: Introductionmentioning
confidence: 99%